Age and genesis of the high metamorphic grade Kultanummi gold prospect, southern Finland - Heiskanen, Niko (My University, 2025)
Bedrock of southern Finland is known for hosting multiple major gold deposits, which have been formed during Svecofennian orogeny ca. 1.92 – 1.79 Ga ago. It can be divided into two major phases: the Fennian (1.89 – 1.86 Ga) and Svecobaltic (1.83 – 1.79 Ga). During Fennian phase the majority of the crust was formed, but the metamorphic peak in southern Finland was achieved during Svecobaltic phase. An extensional period is interpreted between the major orogenic stages related to orogenic collapse. Kultanummi prospect is located near the city of Salo, and it is part of the Uusimaa Belt. It has been studied by Geological Survey of Finland (GTK) in early 2000s including a master’s thesis focusing on the local geology. However, the age relationships compared to geological evolution of southern Finland and the possible deposit type are still unclear. In this study these two things were studied, and formation of mineralization was attempted to be linked to the evolution of regional bedrock. Field work was conducted in the Kultanummi area during Spring 2024, and from the collected samples, several thin sections were made. From these thin sections the most suitable ones were selected for scanning electron microscope analysis. With this the suitable minerals for age determination were studied, i.e. zircon, monazite and rutile. Minerals were dated with U-Pb method with laser-ablated inductively coupled mass spectrometer in Geological Survey of Finland research laboratory at Espoo. Based on the results on this study, several age populations can be interpreted from Kultanummi. Firstly, zircon populations show age populations related to earlier events before Svecofennian orogeny (ca. 2.71 – 1.91 Ga) and furthermore ages related to Fennian phase (ca. 1.88 Ga) and extensional stage (ca. 1.86 Ga). Secondly, monazite age populations also show some ages related to Fennian phase (ca. 1.87 Ga), but they mainly show ages related to metamorphic peak event of Uusimaa Belt (ca. 1.815 Ga) during Svecobaltic phase and hydrothermal activity (ca. 1.79 Ga) after the metamorphic peak. Thirdly, single rutile population shows ages related to same hydrothermal activity (ca. 1.78 Ga) than one monazite population. Kultanummi is untypical gold prospect compared to other gold prospects in southern Finland due to its high metamorphic grade and unusual mineralogy, but it can be interpreted to represent orogenic gold deposit with Al-rich fluid. Gold in Kultanummi is closely associated with sillimanite- and cordierite-rich lithologies and it tends to be structurally controlled. Sillimanite is considered to be an alteration product from Al-rich fluid, and this fluid activity is interpreted to occurred after 1.80 Ga. Based on the results, Kultanummi is interpreted to be an orogenic gold deposit, which has been formed from Al-rich fluid activity between 1.80 – 1.77 Ga.

Etelä-Suomen kallioperästä tunnetaan useita huomattavia kultakohteita, jotka ovat muodostuneet Svekofennisen orogenian aikana n. 1,92–1,79 miljardia vuotta sitten. Siitä voidaan erottaa kaksi päävaihetta, jotka ovat Fennian (1,89–1,86 Ga) ja Svekobaltian (1,83–1,79 Ga) vaiheet. Suurin osa kallioperästä on muodostunut Fennian vaiheen aikana, mutta Etelä-Suomen metamorfinen huippuvaihe on saavutettu Svekobaltian vaiheen aikana. Näiden kahden vaiheen välissä on tulkittu olevan ekstensionaalinen vaihe, jonka on katsottu liittyvän orogeeniseen romahdukseen. Kultanummen kultaesiintymä sijaitsee lähellä Salon kaupunkia ja se on osa Uudenmaan jaksoa. Sitä on tutkittu Geologian tutkimuskeskuksen (GTK) toimesta 2000-luvun alussa, ja yksi pro gradu -tutkielma tehtiin siellä samaan aikaan. Aiemmista tutkimuksista huolimatta Kultanummen mineralisaation ikä ja mahdollinen esiintymätyyppi eivät ole selvillä. Tämän tutkimuksen tarkoitus oli selvittää näitä kahta edellä mainittua asiaa sekä yhdistää mineralisaation muodostuminen alueelliseen kallioperän kehitykseen. Kenttätyöt toteutettiin keväällä 2024, ja kentältä kerätyistä näytteistä tehtiin ohuthieet, joista valittiin edustavimmat jatkotutkimuksia varten elektronimikroskoopille. Tämän avulla tunnistettiin ikämääritettäviä mineraaleja, kuten zirkoneja, monatsiittia ja rutiilia. Mineraalit ikämääritettiin U-Pb menetelmällä laserherätteisellä induktiivisestikytketyllä massaspektrometrilla GTK:n Espoon laboratoriossa. Saatujen tulosten perusteella Kultanummelta voidaan havaita eri ikäpopulaatioita. Ensiksi, zirkoneista on havaittavissa ikäpopulaatiot liittyen Svekofennistä orogeniaa edeltäviin tapahtumiin (n. 2,71–1,91 Ga), Svekofennisen orogenian Fennian vaiheeseen (n. 1,88 Ga) ja tämän jälkeiseen ekstensionaaliseen vaiheeseen (n. 1,86 Ga). Toiseksi, monatsiiteista on havaittavissa ikäpopulaatiot liittyen Fennian vaiheeseen (n. 1,87 Ga), Uudenmaan jakson metamorfiseen huippuvaiheeseen (n. 1,815 Ga) ja tämän jälkeiseen fluiditoimintaan (n. 1,79 Ga). Kolmanneksi, rutiileista on havaittavissa vain yksi ikäpopulaatio liittyen fluiditoimintaan (n. 1,78 Ga) monatsiittien tapaan. Kultanummi on epätyypillinen kultaesiintymä verrattuna muihin Etelä-Suomen kultakohteisiin, johtuen sen korkeasta metamorfoosiasteesta ja epätyypillisestä mineralogiasta. Kultamineralisaatio on läheisesti kytköksissä sillimaniitti- ja kordieriitti-rikkaiden litologioiden kanssa ja siinä on havaittavissa rakennekontrolli. Sillimaniitin voidaan tulkita olevan muuttumismineraali ja se on syntynyt fluiditoiminnan johdosta 1,80 Ga jälkeen. Tulosten perusteella esiintymätyyppi edustaa orogeenistä kultaesiintymää, joka on muodostunut Al-rikkaan fluiditoiminnan seurauksena noin 1,80–1,77 Ga.
Keywords: Svecofennian orogeny, orogenic gold, geochronology, U-Pb dating, LA-ICP-MS